From Lewis Carroll’s “Alice in Wonderland” to “Alice on social media”: Approaches of fantasy as a real experience in Cyberspace - Hadjieustathiou, Marilena; Ioannou, Andreas; Karfitsa, Aggelikh; Paliari, Anna; Skantzouri, Maria (Homo Virtualis, 2022)
In the present study, we implement the theory of Hermeneutics in order to understand the element of reality in the virtual world experience. We attempted to formulate cases on the user experiences and interpret them, as described in existing research and reflected on social media. Our focus topic consists of the use of imagination and its contribution to the construction of identity, behavior and relationships in the virtual environment of social media. We also make references to the elements of irrationality and time, two variables that are likely to affect the way users perceive reality. The online methodological tools and programs Concept-mapping and Social Network Visualiser were used in order to collect and capture the mentioned and further related concepts as well. The results of the study include possible conceptual correlations in social media, for which we argue that their virtuality depends on the actions of the user, and individual conclusions about the function of the imagination, which we consider to be an integral part of conception, implementation and quality of reality.